2009
DOI: 10.1167/9.7.13
|View full text |Cite
|
Sign up to set email alerts
|

Spatial contrast sensitivity and grating acuity of barn owls

Abstract: The eyes of barn owls (Tyto alba pratincola) display very little aberrations, and have thus excellent optical quality. In a series of behavioral experiments, we tested whether this presumably beneficial feature is also reflected at a perceptual level in this species. As fundamental indicators for visual performance, the spatial contrast sensitivity function (CSF) and grating acuity were measured in two barn owls with psychophysical techniques. Stimulus luminance was 2.7 cd/m(2). The CSF found here renders the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 56 publications
6
41
0
Order By: Relevance
“…The Weber fraction for human LWS cone photoreceptors has been suggested to be 0.018 (Wyszecki and Stiles, 2000), which is much smaller than the Weber fraction for bird LWS cones (0.06 for chickens and 0.1 for Leiothrix and budgerigars). This difference could explain why we found no obvious difference in colour discrimination threshold between humans and birds and may also help to explain why birds generally have lower contrast sensitivity than humans (Ghim and Hodos, 2006;Gover et al, 2009;Harmening et al, 2009;Lind et al, 2012).…”
Section: Dark Noisementioning
confidence: 74%
“…The Weber fraction for human LWS cone photoreceptors has been suggested to be 0.018 (Wyszecki and Stiles, 2000), which is much smaller than the Weber fraction for bird LWS cones (0.06 for chickens and 0.1 for Leiothrix and budgerigars). This difference could explain why we found no obvious difference in colour discrimination threshold between humans and birds and may also help to explain why birds generally have lower contrast sensitivity than humans (Ghim and Hodos, 2006;Gover et al, 2009;Harmening et al, 2009;Lind et al, 2012).…”
Section: Dark Noisementioning
confidence: 74%
“…Martin and Gordon (1974) and Harmening et al (2009) used behavioral methods to study the contrast sensitivity of three species of owls (Tyto alba pranticola, Strix aluco, and Bubo virginianos). Harmening et al (2009) found a contrast sensitivity peak of 1-2 cpd and visual acuity of 3-4 cpd. Ghim and Hodos (2006) used pattern electroretinography to compare the CSF of several bird species, including falcons (Falco sparvarius), owls (Tyto alba), European starlings (Sturnus vulgaris), quails (Coturnix coturnix japonica), red-bellied woodpeckers (Melanerpes carolinus), and pigeons (Columbia livia).…”
Section: Luminance Spatial Contrast Sensitivity Of Birdsmentioning
confidence: 99%
“…Its behavioral acuity (12.6 cyc/°) (Hahmann and Güntürkün, 1993) surpasses many mammalian species (Van Hooser and Nelson, 2006) and is even three times higher than the barn owl (Harmening et al, 2009). Against the owl, the pigeon Wulst may be less well differentiated in cytoarchitecture (Karten et al, 1973), receives less afferent input from the GLd, and has neurons with larger receptive fields [4.5° (Miceli et al, 1979) vs 1-2°in owls (Pettigrew, 1979)].…”
Section: Lack Of Orientation Maps Despite Orientation Selectivitymentioning
confidence: 99%
“…Particularly, the owl visual Wulst is extensively involved in the interpretation of binocular interaction (Pettigrew and Konishi, 1976;Pettigrew, 1979;Nieder and Wagner, 2001) and additionally performs more complicated functions, such as the representation of illusory contours (Nieder and Wagner, 1999). Despite excellent optics and a well developed visual Wulst, the barn owl's behavioral acuity belongs to the lower end of examined birds (Harmening et al, 2009).…”
Section: Introductionmentioning
confidence: 99%